The joint association of physical activity and sedentary behavior with health-related quality of life among children and adolescents in Mainland China - Shi, Jun; Wang, Xiaorong; Wu, Qiong; Qin, Zhenzhen; Wang, Na; Qiao, Huifen; Xu, Fei (Frontiers in Public Health, 2022)
Objectives To investigate the joint association of physical activity (PA) and sedentary behavior (SB) with health-related quality of life (HRQoL) among children in Mainland China. Methods Children were randomly recruited from primary, junior and senior high schools (graders 4-12) in Nanjing municipality of China in this cross-sectional survey in 2018. The outcome variable, HRQoL, was assessed using the validated Chinese version of Child Health Utility 9D (CHU9D-CHN) instrument. PA and SB were measured using a validated Physical Activity Scale and Food Frequency Questionnaire for Chinese school-aged children. The associations of PA and SB with HRQoL were assessed using mixed-effects linear regression models and reported as mean difference (MD) and 95% confidence interval (CI). Results Totally, 4388 participants completed the survey (response rate=97.6%). After adjustment for potential confounders and class-level clustering effects, relative to those with insufficient PA and prolonged SB, students with insufficient PA and shortened SB (MD=0.054, 95%CI=0.018, 0.089), or children with sufficient PA and prolonged SB (MD=0.034, 95%CI= -0.030, 0.098), or students with sufficient PA and shortened SB (MD=0.083, 95%CI=0.045, 0.120), respectively, reported increased HRQoL scores. Conclusions PA was positively associated with HRQoL and SB was in negative relation to HRQoL. Furthermore, sufficient PA and shortened SB might exert additive influence on HRQoL among children and adolescents in China. This study has public health implications that PA promotion and SB reduction are encouraged to be considered simultaneously for the purpose to maximally improve HRQoL in population-based behavior intervention campaigns among children and adolescents.